Tantangan dan Peluang dalam Manajemen Program Berita di Era Digital : (Studi Kasus di CNN Indonesia TV Jawa Barat) - Prima Arya Bintang; Eni Maryani; Nuryah Asri Sjafirah (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The management of local news programs within Indonesia’s Networked Broadcasting System (Sistem Stasiun Jaringan/SSJ) faces structural challenges amid the transition toward a digital media environment. This study aims to analyze the challenges and opportunities in news program management at CNN Indonesia TV West Java as part of the SSJ in the digital media era. Using a qualitative approach with a case study method, data were collected through in-depth interviews and document analysis to examine local news distribution practices. The findings reveal that local news distribution remains constrained by structural limitations, as reflected in the limited proportion of local news and its placement in low-audience time slots, which restricts audience reach and the flexibility of regional newsrooms to develop local news programs strategically. In response to these limitations, digital platforms such as YouTube and Instagram are utilized as alternative distribution channels. However, this digital adaptation has not been accompanied by adjustments in newsroom work structures, resulting in increased journalists’ workloads due to cross-platform content production demands and repurposing practices. Nevertheless, digital distribution has enhanced the visibility of local news and demonstrates that audience proximity constitutes a strategic opportunity in managing local news in the digital era. This study highlights the importance of integrating digital distribution strategies with managerial adjustments to enable more adaptive and audience-oriented local news management within the SSJ framework.